Effectiveness of Electronic Health Records (EHR) Use by Nurses: A Literature Review - Fitra Pringgayuda; Faridah Hashim (Pancasakti Journal Of Public Health Science And Research, 2025)
Electronic Health Records (EHR) are progressively implemented in healthcare systems to enhance efficiency, documentation precision, and patient safety. The influence of EHR implementation on nursing practice varies across different environments. This literature analysis sought to assess the efficacy of electronic health record utilization by nurses in clinical documentation, drawing on primary research published from 2015 to 2025. A total of 12 publications were selected following a stringent screening procedure utilizing the SPIDER framework, including various study designs such as observational, longitudinal, and interventional methodologies. The results indicated that EHR improves documentation efficiency and access to clinical information when systems are optimally designed and supplemented with sufficient training. Poor usability and insufficient user engagement result in heightened burden, stress, and diminished quality of care. The successful deployment is intricately connected to system usability, managerial endorsement, and nurse participation in system development. The results underscore the necessity for user-centered design and ongoing organizational dedication to ensure that EHRs facilitate rather than obstruct nursing care.